2008
DOI: 10.1177/1534508408318804
|View full text |Cite
|
Sign up to set email alerts
|

The Learning-to-Learn Strategies of Adolescent Students With Disabilities

Abstract: This study focuses on an examination of the learning-to-learn strategies of seventh-grade students as they highlight, take notes, plan, organize, and write expository texts. Participants consist of 125 students, 41 with disabilities and 84 without disabilities. The results reveal that the students with disabilities have more difficulties in using the learning-to-learn strategies as they read, study, and write expository texts, although neither group is judged to be highly proficient. The implications point to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…For example, Englert et al (2009) found that when teachers developed a program to help students with learning disabilities develop questioning strategies in science class, these students progressed significantly, improving their awareness of textual units and comprehension of texts.…”
Section: Cognitive Load and Note Takingmentioning
confidence: 98%
“…For example, Englert et al (2009) found that when teachers developed a program to help students with learning disabilities develop questioning strategies in science class, these students progressed significantly, improving their awareness of textual units and comprehension of texts.…”
Section: Cognitive Load and Note Takingmentioning
confidence: 98%
“…For individuals with and without disabilities, the aspect of composing expository text is not easily undertaken (Englert et al, 2009; Salahu-Din, Persky, & Miller, 2008). The 2007 National Assessment of Educational Progress provided an appraisal of eighth- and twelfth-graders’ writing skills and determined that only 33% of the participants fell within the proficient range (Salahu-Din et al, 2008).…”
mentioning
confidence: 99%
“…The 2007 National Assessment of Educational Progress provided an appraisal of eighth- and twelfth-graders’ writing skills and determined that only 33% of the participants fell within the proficient range (Salahu-Din et al, 2008). With regard to producing written passages, students with disabilities commonly experience difficulties developing a comprehensive plan, generating sentences beyond listing topical knowledge, and revising compositions further than the correction of grammatical errors (Englert et al, 1988; Englert et al, 2009; Graham & Harris, 2003; Harris, Graham, & Mason, 2003; Hayes & Flower, 1987).…”
mentioning
confidence: 99%
“…• Explicitly teach key vocabulary utilized in content area texts (Fang, 2006), • Supplement students' background knowledge about relevant concepts upon which the new readings are intended to build ), • Provide instruction in making inferences about the relationship among ideas in the text (Englert et al, 2009;Meyer et al, 2010), and • Improve students' metacognitive strategies by having them generate or answer questions while reading as well as monitor their comprehension by paraphrasing or summarizing (Berkeley, Mastropieri, & Scruggs, 2011;Thiede, Anderson, & Therriault, 2003).…”
Section: Reading Instruction For Students With Reading Disabilities: mentioning
confidence: 99%